2020
DOI: 10.1111/jfb.14315
|View full text |Cite
|
Sign up to set email alerts
|

Reliable eDNA detection and quantification of the European weather loach (Misgurnus fossilis)

Abstract: The European weather loach (Misgurnus fossilis) is a cryptic and poorly known fish species of high conservation concern. The species is experiencing dramatic population collapses across its native range to the point of regional extinction. Although environmental DNA (eDNA)‐based approaches offer clear advantages over conventional field methods for monitoring rare and endangered species, accurate detection and quantification remain difficult and quality assessment is often poorly incorporated. In this study, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
83
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 68 publications
(87 citation statements)
references
References 53 publications
2
83
1
1
Order By: Relevance
“…While we observed similar detection sensitivity for qPCR and ddPCR on DNA extracted from crayfish tissue, we had lower detection sensitivity for ddPCR compared to qPCR for the eDNA samples. This contrasts other studies where ddPCR appears to be more sensitive than qPCR for eDNA detection (e.g., Doi et al, 2015b;Hamaguchi et al, 2018;Mauvisseau et al, 2019a;Wood et al, 2019;Brys et al, 2020). In some eDNA samples we observed a reduced amplitude for the ddPCR indicating some inhibition.…”
Section: Efficiency For Edna Detection Of Noble Crayfish -Qpcr Versuscontrasting
confidence: 99%
See 3 more Smart Citations
“…While we observed similar detection sensitivity for qPCR and ddPCR on DNA extracted from crayfish tissue, we had lower detection sensitivity for ddPCR compared to qPCR for the eDNA samples. This contrasts other studies where ddPCR appears to be more sensitive than qPCR for eDNA detection (e.g., Doi et al, 2015b;Hamaguchi et al, 2018;Mauvisseau et al, 2019a;Wood et al, 2019;Brys et al, 2020). In some eDNA samples we observed a reduced amplitude for the ddPCR indicating some inhibition.…”
Section: Efficiency For Edna Detection Of Noble Crayfish -Qpcr Versuscontrasting
confidence: 99%
“…It is commonly reported that ddPCR overcomes the challenges connected to inhibitory substances to a higher extent than qPCR, and displays both higher sensitivity and higher quantification accuracy (Dingle et al, 2013;Rački et al, 2014;Zhao et al, 2016), and several studies have highlighted the benefits of ddPCR for eDNA detection (e.g., Doi et al, 2015a;Hunter et al, 2017;Hamaguchi et al, 2018;Mauvisseau et al, 2019a;Brys et al, 2020). However, while ddPCR offers absolute quantification, the variation in estimated copy numbers increases at low numbers, therefore the LOQ of ddPCR is often within the same range as LOQ for qPCR (Dobnik et al, 2015).…”
Section: Efficiency For Edna Detection Of Noble Crayfish -Qpcr Versusmentioning
confidence: 99%
See 2 more Smart Citations
“…Voor een algemene opvolging van heel wat bekende invasieve probleemsoorten is doelgerichte monitoring nodig op risicolocaties voor introductie. Vaak zijn hiervoor gespecialiseerde methoden vereist, zoals milieu-DNA (stierkikkers, rivierkreeften) (Brys et al 2019(Brys et al , 2020, wildcamera's (wasberen, muntjakken) of specifieke vangtuigen. Er zou een meer actief, officieel surveillancesysteem opgezet moeten worden dat in de professionele monitoring netwerken (zoals de programma's in het kader van Natura 2000 of de KRW) verankerd is.…”
Section: Gevalstudie: Verwijdering Van Een Populatie Pallas' Eekhoornunclassified